2014
DOI: 10.1542/peds.2013-2775
|View full text |Cite
|
Sign up to set email alerts
|

National Trends Over 25 Years in Pediatric Kidney Transplant Outcomes

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Kidney transplantation is the optimal treatment of children with end-stage renal disease. The field of pediatric kidney transplantation has changed over time with regard to immunosuppression, surgical technique, organ allocation policy, and rates of living donor transplantation. WHAT THIS STUDY ADDS:Outcomes after pediatric kidney transplantation in the United States have improved over time, independent of changes in recipient, donor, and transplant characteristics. These improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 180 publications
(145 citation statements)
references
References 45 publications
9
134
2
Order By: Relevance
“…[14] In a recent publication from the USA that reviewed 17 000 paediatric kidney transplants, outcomes were significantly better after 2001, which may be related to better immunosuppression, with 10-year recipient and graft survival rates of 90.5% and 60.2%, respectively. [15] Explanations for the relatively good survival in our cohort, given that it is still a small sample, may reflect the more 'recent' time frame of analysis; higher living donor rates (64%) compared with 24% at RCWMCH and 21% at CMJAH; fewer black children, who have been shown to have poorer graft survival; fewer repeat transplants; and the assumption that socioeconomic circumstances are better in patients accessing a funded healthcare environment. [16] SKP transplantation is considered the treatment of choice for type 1 diabetics with end-stage kidney disease who are <50 years of age.…”
Section: Researchmentioning
confidence: 98%
“…[14] In a recent publication from the USA that reviewed 17 000 paediatric kidney transplants, outcomes were significantly better after 2001, which may be related to better immunosuppression, with 10-year recipient and graft survival rates of 90.5% and 60.2%, respectively. [15] Explanations for the relatively good survival in our cohort, given that it is still a small sample, may reflect the more 'recent' time frame of analysis; higher living donor rates (64%) compared with 24% at RCWMCH and 21% at CMJAH; fewer black children, who have been shown to have poorer graft survival; fewer repeat transplants; and the assumption that socioeconomic circumstances are better in patients accessing a funded healthcare environment. [16] SKP transplantation is considered the treatment of choice for type 1 diabetics with end-stage kidney disease who are <50 years of age.…”
Section: Researchmentioning
confidence: 98%
“…After this transition from maintenance dialysis to renal transplantation, graft survival among the recently transplanted infants was better than that of infants in the past cohort and is consistent with the results of recent single-center reports and those published by the Scientific Registry of Transplant Recipients. [6][7][8]27 Because graft survival has consistently improved among all pediatric age groups over the past few decades as a result of a variety of factors, including improved immunosuppression and surgical technique and a better understanding of transplant-related immunology, 28 there is every reason to expect that transplant outcomes will continue to improve overall and among the youngest patients.…”
Section: Figurementioning
confidence: 99%
“…Our observed patient survival is consistent with the outcomes described in the literature. 2,3 Further research is needed on this topic, and large-scale studies are indicated. …”
Section: Discussionmentioning
confidence: 99%